A conceptual framework: The effect of saving planning, debt investment planning and retirement planning on personal financial planning among Amanah Ikhtiar Members (AIM), in Tumpat - Ab. Rahman , Siti Maziah; Abdullah , Maznah; Nik Ismail , Nik Rozhan; Usman , Zaihan; Md Apandi , Hassanul Firman; Muhammad , Mohd Zainuri; Yusoff , Azahar (Journal of Islamic, Social, Economics and Development, 2025)
This conceptual paper aims to explore the effect of financial literacy on Personal Financial Planning, focusing on the role of Islamic financial concepts, principles, and practices in enhancing financial decision-making and management among individuals. Drawing upon existing literature from Islamic finance, financial literacy, and Personal Financial Planning, we propose a framework that sheds light on the factors influencing the relationship between financial literacy and Personal Financial Planning. People's financial security is becoming a serious concern in light of the global economic climate. Acquiring expertise and comprehension of financial issues is the essence of financial literacy. This study's goal is to ascertain the financial literacy level of the AIM group, which consists of members of the TUMPAT AMANAH IKHTIAR MALAYSIA (AIM) , as well as the impact of financial literacy on Investment Planning, debt management strategies, savings plans, and retirement plans. Four independent variables make up the framework of this study: investment decision, debt planning, retirement plan, and savings plan. We then examine the concept of financial literacy, defining its key elements and highlighting its importance in enabling individuals to make informed financial decisions and manage their finances effectively. Subsequently, we explore the linkages between financial literacy and Personal Financial Planning, analyzing the ways in which Islamic financial concepts, principles, and practices can positively affect Personal Financial Planning practices.